PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS MOBILE AUGMENTED REALITY UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA SMP PADA MATERI LAPISAN BUMI DAN BENCANA - Putri, Unggani Filzana; M. Nor, M. Nor; Sahal, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to describe students' cognitive learning outcomes in studying physics by using Mobile Augmented Reality-based learning media on the material of the earth's layers and disasters and to determine the differences in students' cognitive learning outcomes between the class that uses Mobile Augmented Reality-based learning media and the class that does not use the Mobile Augmented Reality-based learning media in the seventh grade of junior high school (SMP). The problem in this study is the low student learning outcomes due to the lack of learning media variation so that the students cannot fully understand and become less interested in the learning process. The research was conducted in grades VII A and VII B of SMP Negeri 03 Guguak District in April-December 2021 with a total of 30 students. This type of research is experimental research with Intact Group Comparison design. Class VII B as the experimental class became the class where the learning media based on Mobile Augmented Reality was applied, while class VII A as the control class did not use the Mobile Augmented Reality-based learning media. The data collection technique in this study was collected by giving a posttest to the experimental class and the control class. The data analyses used in this research are descriptive and inferential analysis. The results showed that the use of Mobile Augmented Reality-based media could improve the students' cognitive learning outcomes on the earth's layers and disasters materials with an average percentage of students' absorption is 75% of the students are in the good category and the effectiveness level is in the effective category. The significance value of the T-Test is p (0.010) <0.05, so it can be concluded that there is a significant difference in students' cognitive learning outcomes between the experimental class and the control class.Keywords: Learning Media, Mobile Augmented Reality, Cognitive Learning Result